Navigating Faith in the Digital Age: The Role of Technology in Shaping Gen-Z's Religious Perspectives - Masripah; Anisah, Ani Siti; Irvani, Asep Irvan (Indonesian Scientific Publication, 2024)
This study aims to analyze the impact of digital technology on contemporary Islamic thought and religious practices among Generation Z (Gen-Z). Employing a Mixed Methods Research (MMR) approach with a Triangulation design, the study involved 264 respondents using a five-point Likert scale questionnaire and semi-structured interviews with five key informants. The findings reveal that digital technology positively influences contemporary Islamic thought by 56.4%, religious practices by 50.2%, and the combination of both by 51.5%. Generation Z utilizes technology such as social media, religious applications, and online forums to understand Islam contextually and flexibly. They leverage technology to explore contemporary issues such as moderation and pluralism while supporting daily religious practices through digital Qur'an applications and online studies. However, the study also identifies challenges, including the risk of inaccurate information, exposure to radicalization, and potential impacts on religious traditions and spiritual depth. This research underscores the need for religion-based digital literacy to help Generation Z utilize technology wisely, with guidance from religious leaders and parents and the development of relevant religious applications. With a strategic approach, digital technology can effectively strengthen a moderate, inclusive, and contextually relevant understanding of Islam in the digital era. The findings of this study are expected to provide a foundation for developing strategies in Islamic education and dakwah tailored to support the spiritual lives of Generation Z in the future.